The Effect of Plyometric Training on Forehand Ability in Pickleball - Ridlo, Azi Faiz; Basri, Hasan; Amir Maulana; Rizki Ridha kusuma (Universitas PGRI Palembang, 2025)
This study aimed to determine the effect of Plyometric Exercise on improving forehand in pickleball, focusing on the age of 15-18 years. The research conducted was quantitative method with quasi-experiment with pre-test and post-test non-equivalent to control the group design. The respondents of this study were 40 pickleball athletes aged 15–18 years. They were divided into two groups, of which 20 respondents were in the experimental group. While the control subjects numbered 20 people. The research instrument used a forehand test on pickleball. The data was analyzed with the SPSS 26 application. The results of this study showed that the value of t = 41.68, df = 20 and its significance (2 tailed) or p-value = 0.000 < 0.05. Thus the descriptive statistical results with 20 experimental subjects showed an average of 18.95, and after they were given treatment, the post-test results showed a mean of 35.05. This shows that descriptively obtained differences before and after treatment. Thus, the descriptive statistical results for the 20 control subjects were an average of 18.20, and after treatment the average post-test result was 22.21. This shows that descriptively obtained differences before and after being given treatment. Therefore, it can be ascertained that this plyometric exercise is effective in increasing the topspin groundstroke ability of junior tennis athletes aged 15-18 years.